miRNA-mRNA integrative profiling in canine tubulopapillary mammary carcinoma - Nayra Cristina Herreira do Valle; Matheus Fujimura Soares; Natália Francisco Scaramele; Amanda de Oliveira Furlan; Maria Fernanda da Silva Lopes; Juliana de Souza Felix; Fernando Vissani Fernandes; Vinicius Aquiles Gomes Zamboni; Igor Luiz Salardani Senhorello; Alexandre Lima de Andrade; Flavia Lombardi Lopes (Research in Veterinary Science, 2026)

Deciphering the complex life cycle and partial migration of an ecological engineer and critical Neotropical fishery species, Prochilodus costatus - Alexandre Peressin; João de Magalhães Lopes; Francisco Ricardo Andrade Neto; Gilmara Junqueira Machado; Carlos Bernardo Mascarenhas Alves; Luis David Solis Murgas; Paulo Santos Pompeu (Journal of Fish Biology, 2026)
Understanding complex migration patterns, including drivers of partial migration and habitat use, is challenging but essential for conservation, as it determines a species' adaptative capacity in the face of environmental change and anthropogenic threats. Therefore, we investigated the traits of partial migration and spawning use in the long‐distance migratory and ecosystem engineering fish Prochilodus costatus (pioa). Data from 200 adult individuals tagged with radio transmitters at their feeding and spawning sites, combined with egg and larvae sampling identified through metabarcoding, revealed strong fidelity to both feeding and spawning sites. Providing a comprehensive overview of the pioa life cycle, this study shows that only fish present at specific upstream sites reproduce, indicating that populations isolated downstream, or whose migrations are blocked for any reason, fail to reproduce. Adults may also remain resident at spawning grounds, but these residents are smaller and have lower body condition, suggesting suboptimal feeding conditions at these sites. Use of spawning grounds was not evenly distributed: approximately half of the tagged fish performed annual upstream reproductive migrations, with 58.6% migrating to Bambuí River and 41.49% to the upper Sao Francisco River basin spawning sites, displaying homing behaviour. Hormone levels, body weight, and condition factor were not related to migration decisions, suggesting that the drivers of partial migration remain unclear. Our findings reveal putative population structuring, site fidelity, habitat use, and partial migratory behaviours shared with other phylogenetically distant fish groups, indicating that these results may be generalizable to other Neotropical migratory species.

Antibacterial and antibiofilm activity of ruthenium polypyridine complex against Staphylococcus strains - Leonardo Silva de Sousa; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Felipe Diógenes Abreu; Eduardo Henrique Silva Sousa; Idalina Maria Moreira de Carvalho; Débora S. C. M. Castelo-Branco; Mayron Alves de Vasconcelos; Edson Holanda Teixeira (Biofouling, 2025)

Enhanced antimicrobial and antibiofilm activities of ruthenium complexes with fluorine- and bromine-substituted ligands against staphylococcal strains - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Isa Maria Ferreira Azevedo; Tatiane Gomes da Silva; Paula Victoria Soares; Ellen Araújo Malveira; José Marcos da Silveira Carvalho; Débora S. C. M. Castelo-Branco; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2025)

Contamination status and evaluation of metal pollution indexes in sediments from shrimp farming in the Lower São Francisco River region, Northeast Brazil - Larissa Santos Xavier; Joel Marques da Silva; Andrielle dos Santos de Jesus; João Batista Pereira; Amanda Silva de Jesus; Marcos Vinicius Teles Gomes; Sarah Adriana Rocha Soares; Andrea Novelli; Elisângela Andrade Passos; Rennan Geovanny Oliveira Araujo; Carlos Alexandre Borges Garcia; Felipo Obed Correia; et al. (Journal of Soils and Sediments, 2025)

Establishment of Psychotria viridis Ruiz & Pav. callus cultures, plantlet regeneration and in vitro production of the hallucinogenic indole alkaloid N,N-dimethyltryptamine - Camila Moreno Lopes de Andrade; Beatriz Aparecida Passos Paranhos Bismara; Fabiana Pereira Santos; Maurício Yonamine; José Alexandre de Souza Crippa; Jaime Eduardo Cecílio Hallak; Fernando Henrique Ferrari Alves; Moacir Pasqual; Vanessa Cristina Stein (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Evaluation of metals in surface sediments from shrimp farming areas in the estuarine region of the Baixo São Francisco, in Northeastern Brazil - Larissa Santos Xavier; Raynne Aparecida de Sousa Pires; Marcos Vinicius Teles Gomes; Elisângela Andrade Passos; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Felipo Obed Correia; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Evaluation of shrimp farming impacts on the water quality of the Lower São Francisco watershed region, Brazil - Rômulo André Santos Silva; Gustavo Andrade Araujo Oliveira; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Marcos Vinicius Teles Gomes; Adnívia Santos Costa Monteiro; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Antibacterial and Antibiofilm Activity of Croton urticifolius Lam. Essential Oil Via Membrane Disruption - Ellen Araújo Malveira; Aluska Kelly A. Nunes; Alexandre Lopes Andrade; Gabriel Lucas Carvalho Melo; Wildson Max Barbosa da Silva; Selene Maia de Morais; Hélcio Silva dos Santos; Leandro Bezerra de Lima; Cynthia Cavalcanti de Albuquerque; Diego Nathan do Nascimento Souza; Edson Holanda Teixeira; Mayron Alves de Vasconcelos (Current Microbiology, 2024)

Lippia grata Essential Oil Acts Synergistically with Ampicillin Against Staphylococcus aureus and its Biofilm - Anderson Paulo Rodrigues Lopes; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Leonardo Silva de Sousa; Ellen Araújo Malveira; Francisco Fábio Mesquita Oliveira; Cynthia Cavalcanti de Albuquerque; Edson Holanda Teixeira; Mayron Alves de Vasconcelos (Current Microbiology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Migratory behavior of Prochilodus argenteus in the São Francisco River Basin, Brazil - Alexandre Peressin; João de Magalhães Lopes; Lídia Wouters; Francisco Ricardo Andrade Neto; Carlos Bernardo Mascarenhas Alves; Paulo Santos Pompeu (Fisheries Management and Ecology, 2024)
The migratory behavior and spawning of Curimatá‐pacu ( Prochilodus argenteus ) were assessed in a free‐flowing remnant spanning approximately 450 km. This evaluation was conducted using radio‐tagging and egg sampling, with identification performed through metabarcoding techniques. Among the studied individuals, half migrated 100–365 km upstream, primarily in response to the initial rise in river discharge at the onset of the wet season. Conversely, the remaining fish did not exhibit upstream movement, indicating a partial migratory behavior. The presence of eggs exclusively in the headwaters suggests that breeding occurred solely among fish inhabiting the upstream sites. The observed migratory traits resembled those of other congeneric species.

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

Antimicrobial and Antibiofilm Activity of Synthetic Peptide [W7]KR12-KAEK Against Enterococcus faecalis Strains - Mayron Alves Vasconcelos; Bruno Rocha da Silva; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Francisco Flávio Vasconcelos Evaristo; Francisco Vassiliepe Sousa Arruda; Esteban Nicolás Lorenzón; Eduardo Maffud Cilli; Edson Holanda Teixeira (Current Microbiology, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Treatments for the control of Neoechinorhynchus buttnerae (Acanthocephala) in tambaqui Colossoma macropomum - Bruna Rafaela Caetano Nunes; Yuri Vinicius de Andrade Lopes; Ricardo Henrique B. de Souza; Raul Dirceu Pazdiora; Thiago Tetsuo Ushizima; Simone Paiva Medeiros; Lorrayne Tavares Corrêa; Igor Izidoro Cardoso; Matheus Vitor Vieira Andrade; Patricia Oliveira Maciel-Honda; Edsandra Campos Chagas; Fernanda de Alexandre Sebastião (Aquaculture International, 2023)

Antimicrobial, Antibiofilm Activities and Synergic Effect of Triterpene 3β,6β,16β-trihydroxyilup-20(29)-ene Isolated from Combretum leprosum Leaves Against Staphylococcus Strains - Edson Holanda Teixeira; Alexandre Lopes Andrade; Rafael Pereira; Livia Pontes Farias; Gabrieli Sobral Monteiro; Marcia Machado Marinho; Emmanuel Silva Marinho; Hélcio Silva Santos; Mayron Alves de Vasconcelos (Current Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Chemical composition determination and evaluation of the antibacterial activity of essential oils from Ruellia asperula (Mart. Ex Ness) Lindau and Ruellia paniculata L. against oral streptococci - Ariana Azevedo Vasconcelos; Idia Nara de Sousa Veras; Mayron Alves de Vasconcelos; Alexandre Lopes Andrade; Hélcio Silva dos Santos; Paulo Nogueira Bandeira; Elnatan Bezerra de Souza; Maria Rose Jane Ribeiro Albuquerque; Edson Holanda Teixeira (Natural Product Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Wound healing activity of lectin isolated from seeds of Centrolobium microchaete Mart. ex Benth. on cutaneous wounds in mice - Luiz Gonzaga do Nascimento Neto; Mayron Alves de Vasconcelos; Aryane de Azevedo Pinheiro; Ana Patrícia Magalhães Ramos; Renally Barbosa da Silva; Alexandre Lopes Andrade; Francisco Vassiliepe Sousa Arruda; José Ajax Nogueira Queiroz; Edson Holanda Teixeira (Natural Product Research, 2022)

A chloroacetamide derivative as a potent candidate for fusariosis treatment - Gabriella da Rosa Monte Machado; Stefânia Neiva Lavorato; William Lopes; Marilene Henning Vainstein; Mário Lettieri Teixeira; Ricardo José Alves; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Evaluation of Antimicrobial and Antioxidant Potential of Essential Oil from Croton piauhiensis Müll. Arg. - Jean Parcelli Costa do Vale; Mayron Alves Vasconcelos; Francisco Vassiliepe Sousa Arruda; Nairley Cardoso Sá Firmino; Anna Luísa Pereira; Alexandre Lopes Andrade; Silvana Saker-Sampaio; Alexandre Holanda Sampaio; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Márcia Machado Marinho; Tigressa Helena Soares Rodrigues; et al. (Current Microbiology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Antimicrobial activity and antibiotic synergy of a biphosphinic ruthenium complex against clinically relevant bacteria - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Francisco Vassiliepe de Sousa Arruda; Luiz Gonzaga do Nascimento Neto; José Marcos da Silveira Carvalho; Ana Claudia Silva Gondim; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2020)

Structure-based design of δ-lactones for new antifungal drug development: susceptibility, mechanism of action, and toxicity - Daiane F. Dalla Lana; Ânderson R. Carvalho; William Lopes; Marilene H. Vainstein; Luciano S. P. Guimarães; Mário L. Teixeira; Luis F. S. de Oliveira; Michel M. Machado; Saulo F. de Andrade; Marcus M. Sá; Theo V. C. Russo; Gustavo P. Silveira; et al. (Folia Microbiologica, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Antibacterial effect on mature biofilms of oral streptococci and antioxidant activity of 3β,6β,16β-trihydroxylup-20(29)-ene from Combretum leprosum - Francisco Flávio Vasconcelos Evaristo; Mayron Alves de Vasconcelos; Francisco Vassiliepe Sousa Arruda; Anna Luísa Pereira; Alexandre Lopes Andrade; Daniel Barroso de Alencar; Mariana Ferreira do Nascimento; Alexandre Holanda Sampaio; Silvana Saker-Sampaio; Paulo Nogueira Bandeira; Hélcio Silva dos Santos; Edson Holanda Teixeira (Medicinal Chemistry Research, 2017)

Reaeration Coefficient Estimate: New Parameter for Predictive Equations - Julio Cesar de Souza Inácio Gonçalves; Alexandre Silveira; Guilherme Barbosa Lopes Júnior; Mário Sérgio da Luz; André Luiz Andrade Simões (Water, Air, & Soil Pollution, 2017)